2021
DOI: 10.24191/smrj.v18i1.5783
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Cooperative Learning in Teaching and Learning in Central Malaysia High School

Abstract: The purpose of this study was to investigate the current understanding and perception of cooperative learning in teaching and learning in Malaysia High School. This study emphasized on teachers’ views on cooperative learning approach to support their students’ teaching and learning in classroom. The study uses the qualitative approach involving 10 academic staff of a local high school located at Subang Jaya, Selangor by using semi structured interview method. The findings showed positive perceptions and intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous study has shown that although cooperative learning strategies have been introduced to teachers, there is still a moderate level of application [7]. Besides, teachers have difficulties in implementing cooperative learning due to a lack of understanding of the strategy and embedding curriculums with cooperative learning implementation [8], and classroom management [9], [10]. Additionally, in this digital era of education, the integration of technology in teaching and learning approaches has a positive impact, especially in boosting pupils' maximum potential [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has shown that although cooperative learning strategies have been introduced to teachers, there is still a moderate level of application [7]. Besides, teachers have difficulties in implementing cooperative learning due to a lack of understanding of the strategy and embedding curriculums with cooperative learning implementation [8], and classroom management [9], [10]. Additionally, in this digital era of education, the integration of technology in teaching and learning approaches has a positive impact, especially in boosting pupils' maximum potential [11].…”
Section: Introductionmentioning
confidence: 99%